The body is not an apology : the power of radical self-love - Taylor, Sonya Renee (Berrett-Koehler Publishers, Inc., 2021)
""To build a world that works for everyone, we must first make the radical decision to love every facet of ourselves. . . . 'The body is not an apology' is the mantra we should all embrace." -Kimberlé Crenshaw, legal scholar and founder and Executive Director, African American Policy Forum"--